Ecological gradients influencing waterbird communities in black water lakes in the anavilhanas archipelago, central Amazonia - Cintra, Renato (International Journal of Ecology, 2020)
For the first time, and in a large spatial scale, the influence of ecological properties on the aquatic bird community of black water lakes in Brazilian Amazonia is evaluated. Bird surveys were conducted in 45 lakes. A total of 3626 individuals in 48 bird species were recorded; of these, 31 are aquatic, and 18 of these are primarily piscivorous. Bird richness and abundance were not significantly related to lake shape and productivity but were influenced by hydrological period (low versus high), water depth, transparency, lake isolation, and habitat richness. Matrices of bird species by lake were subjected to multivariate analyses (NMDS) to evaluate how these parameters influence bird community. The variation in bird species composition was positively correlated to lake depth and isolation and negatively correlated to water transparency and habitat richness. The results indicate that period, lake physical characteristics (depth, water transparency), isolation, and habitat richness are determinants of aquatic bird community composition in the black water lake systems of Amazonia. © Copyright 2012 Renato Cintra.